Processing XML: a rewriting system approach - Simões, Alberto (2010)
SIMÕES, Alberto ; CRUZ, Daniela da ; RAMALHO, José Carlos, ed. lit. – “XATA 2010 XML : associated technologies and applications, 8, Vila do Conde, 2010”. [S.l. : s.n.], 2010. ISBN 978-972-99166-9-4.